A Cross-Sectional Study of Psychosocial Factors and Sickness Presenteeism in Japanese Workers During the COVID-19 Pandemic. Issue 1 (14th October 2021) - Masuda, Masashi; Ishimaru, Tomohiro; Hino, Ayako; Ando, Hajime; Tateishi, Seiichiro; Nagata, Tomohisa; Tsuji, Mayumi; Matsuda, Shinya; Fujino, Yoshihisa
Abstract : Background: We examined the association between socioeconomic and health status, and lifestyle and sickness presenteeism among Japanese workers during the COVID-19 epidemic. Methods: A cross-sectional study using an Internet-monitor survey was conducted in December, 2020 in Japan. Of 33, 302 survey participants, we analyzed 27, 036 participants (13, 814 men and 13, 222 women) who reported experience with sickness presenteeism. Results: The odds ratio (OR) of sickness presenteeism associated with unmarried versus married status was 1.15. Respective figures for other variables were 1.11 for manual laboring work compared to desk work; 1.79 and 2.29 for loss of employment at the time the pandemic began and continuation of unemployment compared with maintaining employment during the pandemic; and 3.34 for a feeling of financial instability compared with stability. Conclusion: The issue of sickness presenteeism has become more prominent under the COVID-19 epidemic.